The clinical features of homozygous alpha 2(I) collagen deficient osteogenesis imperfecta. Issue 4 (August 1984) - Nicholls, A C; Osse, G; Schloon, H G; Lenard, H G; Deak, S; Myers, J C; Prockop, D J; Weigel, W R; Fryer, P; Pope, F M
Abstract : The detailed clinical features and progress of a child with homozygous alpha 2(I) collagen deficiency are described. Clinically, the disease presents as severe progressive Sillence type III osteogenesis imperfecta. The main biochemical defect is the synthesis of an abnormal pro alpha 2(I) chain which does not associate with pro alpha 1(I) chains and therefore is not incorporated into triple helical trimers of type I procollagen which can be used to assemble collagen fibres.